Programming in Visual Basic.Net - Subramanian, Raja. (New Delhi, India : ACME Learning Private Ltd., 2011)
The book (3z(BProgramming in Visual Basic.Net(3y (Bpresents the features of the Visual Basic.Net language, and the procedures of creating the programs using the Visual Basic.Net language in the Microsoft Visual Studio 2005. The step-by-step procedures discussed in this book are useful to the beginners, and reduce the time in learning the Visual Basic.Net language. The experience of using the computer can be gained by browsing through the images captured from the computer screen presented in each chapter. The programs can be developed using the discussion of the features of the Visual Basic.Net language presented in this book without doing lot of work. This facilitates the learning process of the language at high speed. The applications in Visual Basic. Net can be developed by modifying, and extending the source code of the programs presented in this book. This simplifies the creation of new programs. This is similar to the creation of new class derived from the base class that already exists.s
Chapter 1. Introduction to programming in Visual Basic.Net -- Chapter 2. Creating console applications -- Chapter 3. Creating Windows applications -- Chapter 4. Numerical computations -- Chapter 5. Functions and subroutines -- Chapter 6. Programming controls in Windows form -- Chapter 7. Programming classes -- Chapter 8. Object oriented programming -- Chapter 9. Processing directories -- Chapter 10. Processing file -- Chapter 11. Programming threads -- Chapter 12. Programming exceptions -- Chapter 13. Programming events -- Chapter 14. Programming in Asp.Net -- Chapter 15. Programming Windows services -- Chapter 16. Programming controls in Web form -- Chapter 17. Programming Web services -- Chapter 18. Graphics in Visual Basic.Net -- Chapter 19. Programming user controls -- Chapter 20. Creating setup and deployment projects -- Index.
Includes index.
Keywords: MICROSOFT NET FRAMEWORK